2019
DOI: 10.3390/toxins11120679
|View full text |Cite
|
Sign up to set email alerts
|

Crotoxin Conjugated to SBA-15 Nanostructured Mesoporous Silica Induces Long-Last Analgesic Effect in the Neuropathic Pain Model in Mice

Abstract: Neuropathic pain is a disease caused by structural and functional plasticity in central and peripheral sensory pathways that produce alterations in nociceptive processing. Currently, pharmacological treatment for this condition remains a challenge. Crotoxin (CTX), the main neurotoxin of Crotalus durissus terrificus rattlesnake venom, has well described prolonged anti-inflammatory and antinociceptive activities. In spite of its potential benefits, the toxicity of CTX remains a limiting factor for its use. SBA-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Although the mechanisms by which SBA-15 decreases the toxicity of compounds is not clear, the controlled release of them may contribute to that. In accordance, previous studies from our group have demonstrated that SBA-15 allows an increase of CTX dose with non-toxic effects (37).…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although the mechanisms by which SBA-15 decreases the toxicity of compounds is not clear, the controlled release of them may contribute to that. In accordance, previous studies from our group have demonstrated that SBA-15 allows an increase of CTX dose with non-toxic effects (37).…”
Section: Introductionsupporting
confidence: 92%
“…In the in vivo assays, the following compounds were used: 40 mg/kg of CTX (22,44) or 54 mg/kg of CTX:SBA-15 administered by subcutaneous (s.c., 200 ml) route, since SBA-15 conjugation enabled an increase of 35% of CTX non-toxic dosage, as previously demonstrated by our group (37). The animals were treated with 5 doses (1 administration/day for 5 consecutive days) or with a single administration, starting from the 5 th day post-immunization, based on previous results from our group which considered the onset of the first symptom of the disease to start the treatment (pain threshold alteration that occurred in the 4 th day after immunization) (45).…”
Section: Preparation Of the Complex (Ctx:sba-15) And Treatmentsupporting
confidence: 73%
See 3 more Smart Citations